COST ACCOUNTING OPTIMIZATION: ANALYZING THE APPLICATION OF FULL COSTING METHOD IN DETERMINING PRODUCTION COSTS AND SELLING PRICES - Antono, Zakia Maulida; Islami, Agnemas Yusoep; Sari, Depina (Jaksya: Jurnal Akuntansi Syariah, 2024)
This study aims to analyze the cost calculation as a basis for setting selling prices in the production processes at CV Nakhoda Nusantara Group. This research employs a qualitative case study approach. The data sources utilized in this study include primary data obtained from direct interviews with the owner of CV Nakhoda Nusantara Group and secondary data derived from interviews, supporting documentation, and literature review. Data collection methods include field research and literature review. The data analysis technique involves identifying production costs at CV Nakhoda Nusantara Group and calculating the cost of goods manufactured using the full costing method. This calculation is then compared to the company’s existing cost calculation method, and recommendations are provided for appropriate production costs and selling prices based on the findings. The results of this study indicate that the use of the full costing method for calculating production costs and selling prices at CV Nakhoda Nusantara Group is more suitable, as it reflects the true cost of the products more accurately compared to the simpler method initially employed by the company.